Evaluation of apical microleakage of teeth sealed with four different root canal sealers (Journal of Applied Oral Science, 2006)
OBJECTIVES: to compare the apical sealing ability of four root canal sealers. MATERIAL AND METHODS: forty extracted human maxillary canines were instrumented 1 mm short of the anatomical apex and randomly assigned to four groups (n=10), according to the root canal sealer used for obturation: Endofill, AH Plus, EndoREZ and Epiphany. Root canals were obturated with gutta-percha points, except for the Epiphany group, in which resin points (Resilon) were used. The teeth were immersed in India ink for seven days and clarified using methyl salicylate. The extent of apical dye penetration was measured with a measuroscope in all aspects of the canal. RESULTS: AH Plus (0.02 mm ± 0.07), Epiphany (0.00 mm ± 0.00) and EndoREZ (0.32 mm ± 0.62) did not differ statistically to each other (p>;0.01). EndoFill presented the highest dye penetration mean (0.83 mm ± 0.73) and was statistically different from the other sealers (p